(untitled) (American Journal of Islam and Society, 2011)
Contributors to the volume, Raudvere and Gaši, skillfully note that “cherished, unfamiliar or rejected—attitudes of Sufism are seldom neutral” (163). If one traces the evolution of Sufism to Western lands, this aneutrality is accentuated. Thus, Sufism in the West is understandably a growing if understudied field. There is a dearth of surveys on the topic, and this makes additional attention to global networking and locality especially welcome. The authors seek to challenge the romantic and literary biases of Orientalist scholarship, and the eleven chapters rise to the occasion because most focus on particular living Sufi communities. The opening chapters set the methodological tone. In the Introduction, the editors emphasize “Sufism as a lived religion” and they rightly acknowledge that Sufism often acts “as a bridge between Eastern and Western spiritual or mystical philosophy” (4). In Chapter 2, Peter Beyer uses the term glocalization while arguing that “as globalized structures, religions are no longer . . . regional affairs which can be understood primarily with reference to a particular core region” (13). He narrates a story of two Canadian Muslim women who might experience different kinds of belief and practice on a spectrum of religiosity. Strangely, however, only once in the article does he mention “Sufism,” and the false dichotomy “Sufi/ scriptural,” which contrasts with the major concepts in the book, such as the primacy of the Qur’an for many Sufis ...